Ownership Dynamics with Large Shareholders: An Empirical Analysis - Donelli, Marcelo; Larrain, Borja; Francisco Urzúa, I. (Journal of Financial and Quantitative Analysis, 2013)
Abstract We study the empirical determinants of corporate ownership dynamics using a unique, hand-collected 20-year data set on the ownership structure of Chilean companies. Controllers’ blockholdings are on average high and stable over time. Controllers still make changes to their holdings through issuance and block trades. In a typical year controllers’ blockholdings decrease (increase) by 5 percentage points or more in approximately 6% (7%) of firms. We find that the separation between controllers’ voting and cash-flow rights reduces the likelihood of ownership dilution. Dilution is preceded by high stock returns and predicts low stock returns in the future when done through issuance.